Assessing the impact of E-business Technology on Supply Chain Management-in Context of Indian Industries - Mamta Sinha; Om Prakash Patel; Amit Sharma (International Journal of Manufacturing and Production Engineering, 2024)
E-business processes and internet technologies offer powerful competitive tools for higher revenues and profits in the industry. Creating an efficient supply chain network is crucial for providing affordable products with high quality, which is essential for gaining a competitive edge. Implementing e-business processes in the supply chain aims to improve overall performance by leveraging information technology advancements for easier coordination and reduced information costs. The research focuses on assessing the impact of e-commerce processes on supply chain management performance, with cost reduction and customer satisfaction as key performance indicators. Operational efficiency, inventory management, logistics, supply chain flexibility, and integration are tested as independent variables affecting supply chain performance. The study reveals that e-business processes significantly impact supply chain performance, including operational efficiency, inventory management, logistics performance, flexibility, and integration. Information technology tools and e-commerce processes create value within the supply chain, leading to improved performance and profitability. The research validates its findings through a survey of top and middle managers in selected Indian automobile companies, with a target size of 115 participants. The study recommends focusing on increasing operational efficiency, coordination, customer satisfaction, and gaining a competitive advantage through enhanced supply chain management capabilities and e-business process implementation.
Keywords: Supply chain management; e-business; inventory management & logistics performance; operational efficiency; supply chain flexibility; supply chain integration; supply chain performance